2007
DOI: 10.1242/jeb.003541
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia in eggs ofAmbystoma maculatum: embryonic development and egg capsule conductance

Abstract: SUMMARY The spotted salamander Ambystoma maculatum breeds in shallow freshwater pools and imbeds its eggs within a common outer jelly matrix that can limit oxygen availability. The eggs are impregnated with the unicellular alga Oophilia amblystomatis, which produces oxygen during the day but consumes oxygen at night. This daily cycle of algal oxygen production drives a diurnal fluctuation of oxygen partial pressure(PO2) within the eggs, the magnitude of which depends on the distance of an egg fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Hutchison and Hammen (14) found no net gain of oxygen from the algae and instead attributed the algal contribution to unknown "growth factors" supplied to the embryo. More refined microelectrode studies have since shown that intracapsular algae do produce a net increase of oxygen (11,12), which confers a meaningful physiological benefit (13). The unexpected intracellular association shown in our study may reveal a benefit to the embryo other than oxygen production.…”
Section: Discussionmentioning
confidence: 56%
“…Hutchison and Hammen (14) found no net gain of oxygen from the algae and instead attributed the algal contribution to unknown "growth factors" supplied to the embryo. More refined microelectrode studies have since shown that intracapsular algae do produce a net increase of oxygen (11,12), which confers a meaningful physiological benefit (13). The unexpected intracellular association shown in our study may reveal a benefit to the embryo other than oxygen production.…”
Section: Discussionmentioning
confidence: 56%
“…Although treatment condition was the primary predictor of embryo length and development throughout the experiment, increased O. amblystomatis abundance alone also had a significant positive effect on both length and development over 30days. These positive effects are likely due to increased oxygen from photosynthesis (Valls and Mills, 2007;Pinder and Friet, 1994) in addition to receiving fixed carbon (discussed below). Eggs maintained in the dark had lower algal populations, and embryos were smaller and less developed.…”
Section: Alga-salamander Interactionsmentioning
confidence: 99%
“…A recent discovery revealed that O. amblystomatis is also endosymbiotic; a portion of algal cells penetrates the embryo near the blastopore and settles within tissues and cells of the embryonic salamander . O. amblystomatis benefits A. maculatum embryos, presumably by increasing oxygen within the egg capsules (Valls and Mills, 2007;Pinder and Friet, 1994), which contributes to faster embryonic growth and development, increased survivorship and more synchronous hatching (Tattersall and Spiegelaar, 2008;Gilbert, 1944;Gilbert, 1942). In turn, O. amblystomatis receives embryonic nitrogenous waste (Goff and Stein, 1978) and possibly CO 2 (Hammen, 1962).…”
Section: Introductionmentioning
confidence: 99%
“…A similar relationship occurs in several species of amphibians, including at least the salamanders Ambystoma gracile, A. jeffersonianum, A. maculatum, A. tigrinum and the frog Rana sylvatica (Bachmann et al 1986;Gilbert 1942Gilbert , 1944Marco and Blaustein 2000;Pinder and Friet 1994). The alga obtains protection from the egg mass and carbon dioxide and nutrients from the embryos, and the embryos benefit from the oxygen produced by the alga (Bachmann et al 1986;Gilbert 1942Gilbert , 1944Hutchison and Hammen 1958;Marco and Blaustein 2000;Pinder and Friet 1994;Valls and Mills 2007). When oxygen levels drop and carbon dioxide levels rise, which can occur in the absence of the alga, spotted salamander embryos develop more slowly, hatch at an earlier developmental stage, develop deformities, and suffer high mortality (Detwiler and Copenhaver 1940;Mills and Barnhart 1999).…”
Section: Introductionmentioning
confidence: 99%